Infrastructure as a Fundamental Dimension of Fulfilling the Rights of Students in Islamic Boarding Schools - Dardiri Hasyim; Darsinah Fajarwati; Anniez Rachmawati Musslifah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Islamic boarding schools (Pesantren), as fundamental Islamic educational institutions in Indonesian society, have full responsibility for the welfare of their students. However, discourse on students’ rights is often more focused on education and religious freedom, while the dimension of the right to safe, adequate, and healthy infrastructure is often neglected. This article aims to analyze the juridical-normative position of infrastructure as a fundamental element in the fulfillment of students’ basic rights. Using a normative legal approach, this study examines the relevant regulatory framework, including Law No. 35 of 2014 on Child Protection, Law No. 20 of 2003 on the National Education System, and Law No. 18 of 2019 on Islamic Boarding Schools. The analysis focuses on how the obligations of the state and Islamic boarding school administrators to provide a safe environment, as mandated by children’s rights to survival, growth, and development, inherently include the provision of infrastructure that meets safety, health, and appropriateness standards. The analysis shows that infrastructure is not merely a supporting facility, but rather a prerequisite for realizing the rights to education, health, and protection from physical and psychological violence. Failure to provide adequate infrastructure constitutes negligence that violates the fundamental rights of Islamic boarding school students. Therefore, this article recommends strengthening the state’s oversight mechanism for infrastructure standards in Islamic boarding schools, while not neglecting institutional autonomy, to ensure comprehensive protection of students’ rights and their fulfillment.